PENGEMBANGAN BUKU SAKU BERBASIS EKOLITERASI UNTUK PESERTA DIDIK KELAS VII - Virnanda, Lyra; Pamungkas Alamsyah, Trian; Nestiadi, Adi (UNIB Press, 2025)
Current environmental problems are often referred to as the triple planetary crisis, where this phenomenon refers to three environmental problems, namely climate change, pollution and biodiversity loss. This phenomenon occurs because of the lack of public concern for the environment. In the midst of the environmental issue phenomenon, a person must be able to protect the environment, the most effective way to produce a generation that cares about the environment can start from the world of education. Based on observations and interviews that have been carried out, the current ecoliteracy skills of students are still not optimal, so this study aims to describe the results of validation from experts and readability tests by students on the development of ecoliteracy-based pocket books for junior high school students in grade VII on the material of interactions between living things and the environment. This study uses the Research and Development method with the ADDIE (Analyze, Design, Development, Implementation and Evaluation) development model, implemented at a Public Junior High School in Serang City with a sample of 30 grade VII students. The analysis was carried out qualitatively and quantitatively with the results of the study showing that ecoliteracy-based pocket books have a